The Metrics of Subjective Wellbeing: Cardinality, Neutrality and Additivity - Kristoffersen, I (My University, 2010)
The use of subjective wellbeing (SWB) data in economic analysis has increased dramatically in recent years and has now become mainstream, despite some lingering concerns about the quality of these data. Although the psychology literature to a certain extent has succeeded in addressing the issues of interpersonal, intertemporal and international comparison of SWB data, the issues of cardinality, neutrality and additivity continue to be contentious among economists. This article surveys the existing literature relevant to these issues in an effort to provide clarity and thus assist SWB data users to develop more robust research designs.
Economic Record
Keywords: Health; Health -- Wellbeing; Health and wellbeing; Health; Wellbeing; Health and wellbeing